Clinical and quality-of-life outcomes after autologous fascial sling and tension-free vaginal tape: a prospective randomized trial - Amaro, João Luiz [UNESP]; Yamamoto, Hamilto Akihissa [UNESP]; Kawano, Paulo Roberto [UNESP]; Barros, Guilherme [UNESP]; Gameiro, Monica O. O. [UNESP]; Agostinho, Aparecido Donizeti [UNESP] (Sociedade Brasileira de Urologia, 2009)
Purpose: Evaluate the impact autologous fascial sling (AFS) and tension-free vaginal tape (TVT) procedures on quality-of-life in incontinent women. Materials and Methods: Forty-one women were randomly distributed into two groups. Group G1 (n = 21), underwent AFS and group G2 (n = 20) TVT implant. The clinical follow up was performed at 1, 6, 12 and 36 months. Results: TVT operative time was significantly shorter than AFS. Cure rates were 71% at 1 month, 57% at 6 and 12 months in G1. In G2, cure rates were 75% at 1 month, 70% at 6 months and 65% at 12 months; there was no significant difference between groups. As regards the satisfaction rate, there was no statistical difference between groups. Analysis of quality of life at 36 months revealed that there was no significant difference between groups. Conclusion: Similar results between AFS and TVT, except for operative time were shorter in TVT.
Keywords: urinary incontinence; stress; suburethral slings; tensionless vaginal tape; random allocation